2018
DOI: 10.3390/mps1040036
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Experimental Factors Affecting Efficacy Testing of Nonporous Plastic Antimicrobial Surfaces

Abstract: Test methods for efficacy assessment of antimicrobial coatings are not modelled on a hospital environment, and instead use high humidity (>90%) high temperature (37 °C), and no airflow. Therefore, an inoculum will not dry, resulting in an antimicrobial surface exhibiting prolonged antimicrobial activity, as moisture is critical to activity. Liquids will dry quicker in a hospital ward, resulting in a reduced antimicrobial efficacy compared to the existing test, rendering the test results artificially favoura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…36,78,92 Other experimental conditions which vary between studies and are known to affect microbial susceptibility to copper include factors that affect inoculum-drying time, like temperature, airow and humidity. 21,88,[93][94][95] Issues with the lack of 'real world' conditions in the industrial standard tests (e.g., ISO 22196, ISO 21702, ISO 846) and the vast collection of modied protocols that now exist as a result have been previously acknowledged and adequately discussed. 21,93,96,97 In addition, the need to take into account the effect of cleaning protocols, surface soiling and wear on material efficacy has been documented.…”
Section: Critical Remarks and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…36,78,92 Other experimental conditions which vary between studies and are known to affect microbial susceptibility to copper include factors that affect inoculum-drying time, like temperature, airow and humidity. 21,88,[93][94][95] Issues with the lack of 'real world' conditions in the industrial standard tests (e.g., ISO 22196, ISO 21702, ISO 846) and the vast collection of modied protocols that now exist as a result have been previously acknowledged and adequately discussed. 21,93,96,97 In addition, the need to take into account the effect of cleaning protocols, surface soiling and wear on material efficacy has been documented.…”
Section: Critical Remarks and Future Perspectivesmentioning
confidence: 99%
“…21,88,[93][94][95] Issues with the lack of 'real world' conditions in the industrial standard tests (e.g., ISO 22196, ISO 21702, ISO 846) and the vast collection of modied protocols that now exist as a result have been previously acknowledged and adequately discussed. 21,93,96,97 In addition, the need to take into account the effect of cleaning protocols, surface soiling and wear on material efficacy has been documented. 93,97 We reiterate previous recommendations calling for updated industrial standard tests which apply environmental parameters more reective of actual conditions within the healthcare setting.…”
Section: Critical Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the micro-patterned surface of films reduces bacterial contamination 7 . To evaluate the antibacterial activity of patterned films different tests can be used and depending on the methodology used, the antibacterial activity results could vary 7 , 16 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Environmental conditions such as these can alter the efficacy of an AMM, and therefore careful consideration should be given when designing or interpreting data from an antimicrobial test method. Humidity-Humidity is an important determinant for the drying time of liquid droplets [79], and therefore is most likely linked to AMM efficacy. In most cases, a reduction in the humidity of the AMM results in a lower antimicrobial efficacy because of the reduction in moisture at the surface through evaporation.…”
Section: Incubation/environmental Factors Affecting the Efficacy Of Antimicrobial Test Methodsmentioning
confidence: 99%